Wellbeing, activity and housing satisfaction – comparing residents with psychiatric disabilities in supported housing and ordinary housing with support - Eklund, Mona (BMC Psychiatry, 2017)
BACKGROUND: The home is imperative for the possibilities for meaningful everyday activities among people with psychiatric disabilities. Knowledge of whether such possibilities vary with type of housing and housing support might reveal areas for improved support. We aimed to compare people with psychiatric disabilities living in supported housing (SH) and ordinary housing with support (OHS) regarding perceived well-being, engaging and satisfying everyday activities, and perceived meaning of activity in one’s accommodation. The importance of these factors and socio-demographics for satisfaction with housing was also explored. METHODS: This naturalistic cross-sectional study was conducted in municipalities and city districts (n = 21) in Sweden, and 155 SH residents and 111 OHS residents participated in an interview that included both self-reports and interviewer ratings. T-test and linear regression analysis were used. RESULTS: The SH group expressed more psychological problems, but better health, quality of life and personal recovery compared to the OHS residents. The latter were rated as having less symptom severity, and higher levels of functioning and activity engagement. Both groups rated themselves as under-occupied in the domains of work, leisure, home management and self-care, but the SH residents less so regarding home management and self-care chores. Although the groups reported similar levels of activity, the SH group were more satisfied with everyday activities and rated their housing higher on possibilities for social interaction and personal development. The groups did not differ on access to activity in their homes. The participants generally reported sufficient access to activity, social interaction and personal development, but those who wanted more personal development in the OHS group outnumbered those who stated they received enough. Higher scores on satisfaction with daily occupations, access to organization and information, wanting more social interaction, and personal recovery predicted high satisfaction with housing in the regression model. CONCLUSION: The fact that health, quality of life and recovery were rated higher by the SH group, despite lower interviewer-ratings on symptoms and level of functioning, might partly be explained by better access to social interaction and personal development in the SH context. This should be acknowledged when planning the support to people who receive OHS.